KESETARAAN GENDER: POSISI KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Suhada Suhada (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2019)
This paper aims to describe women's leadership and gender equality in Islam which is often a controversial issue in Islamic societies. This type of research is library research with a descriptive analysis approach. Sources of data in research can be divided into two types, namely: primary in the form of undergraduate work that discusses the interpretation of leadership and gender equality and secondary in the form of books and scientific works related to research material. This research concludes that a leader is a figure who develops a functional task to oversee the process in order to influence the thoughts, behavior and feelings of others, both groups and individuals towards a common goal. In Islam, there are several principles of leadership, namely: responsibility, monotheism, deliberation, and fairness. Women's leadership is often a controversial issue in Islamic societies, some support and some refuse. Meanwhile, in the perspective of gender equality, there is a belief that Islamic religion does not place rights and obligations in human anatomy in opposing positions, rights and obligations are always equal in the eyes of Islam for the two different sexes. Islam upholds the concept of justice for anyone regardless of their gender. Islam is the foremost religion in the effort to free the bondage of tyranny of slavery, equality of rights and never give the prestige of only one sex. Islam was born as a religion that spreads love and affection for anyone.